2022
DOI: 10.1371/journal.pone.0257156
|View full text |Cite
|
Sign up to set email alerts
|

Using mass spectrometry to investigate fluorescent compounds in squirrel fur

Abstract: While an array of taxa are capable of producing fluorescent pigments, fluorescence in mammals is a novel and poorly understood phenomenon. A first step towards understanding the potential adaptive functions of fluorescence in mammals is to develop an understanding of fluorescent compounds, or fluorophores, that are present in fluorescent tissue. Here we use Fourier transform-ion cyclotron resonance mass spectrometry (FT-ICR MS) of flying squirrel fur known to fluoresce under ultraviolet (UV) light to identify … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Kohler et al 10 found that almost all examined individuals of flying squirrels Glaucomys spp. had pink UV reflectance, mostly pronounced ventrally, further assessed by Hughes et al 13 . Anecdotal observations of the rodents Melomys, Niviventer, and Rattus showed that some guard hairs reflected bright blue 8 , 9 , 14 .…”
Section: Introductionmentioning
confidence: 93%
“…Kohler et al 10 found that almost all examined individuals of flying squirrels Glaucomys spp. had pink UV reflectance, mostly pronounced ventrally, further assessed by Hughes et al 13 . Anecdotal observations of the rodents Melomys, Niviventer, and Rattus showed that some guard hairs reflected bright blue 8 , 9 , 14 .…”
Section: Introductionmentioning
confidence: 93%
“…In mammals, based on the fact that UV-PL is predominantly observed in crepuscular or nocturnal animals, it was recently hypothesized that it could serve ecological functions in light-deprived environments such as intraspeci c communication or camou age (Kohler et al 2019;Olson et al 2021;Anich et al 2021). These hypotheses have not been tested experimentally and have since been challenged (Hamchand et al 2021;Hughes et al 2021). Moreover, because the species concerned live in a wide range of ecosystems and differ widely in life histories, from the semi-aquatic platypus to the terrestrial springhares and the arboreal ying squirrels, it remains unclear whether UV-PL has indeed a speci c ecological signi cance in nocturnal animals, or is simply incidental to other physiological processes (Lagorio, Cordon & Iriel 2015;Marshall & Johnsen 2017;Hamchand et al 2021;Hughes et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These hypotheses have not been tested experimentally and have since been challenged (Hamchand et al 2021;Hughes et al 2021). Moreover, because the species concerned live in a wide range of ecosystems and differ widely in life histories, from the semi-aquatic platypus to the terrestrial springhares and the arboreal ying squirrels, it remains unclear whether UV-PL has indeed a speci c ecological signi cance in nocturnal animals, or is simply incidental to other physiological processes (Lagorio, Cordon & Iriel 2015;Marshall & Johnsen 2017;Hamchand et al 2021;Hughes et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Live animals in the wild photoluminesced comparably to museum specimens, although they were not compared using the same photographic qualitative scale (Kohler et al 2019). Diurnal nonflying squirrels did not photoluminescence; however, a subsequent study elicited some photoluminescence from both gray squirrel (Sciurus carolinensis) and red squirrel (Tamiasciurus hudsonicus) fur extracts when excited at 350 nm (Hughes et al 2022). Twenty unidentified potential luminophores were also found to be present in the fur of non-photoluminescent squirrels (hinting that non-photoluminescent animals carry the potential luminophores, but they are only activated in photoluminescent animals) and were inconsistently present in the fur of all photoluminescent flying squirrels (Hughes et al 2022).…”
Section: Photoluminescence In Fur: An Historical Accountmentioning
confidence: 99%